Application of STAR Method in English Language Learning at PAUD Nurnaima Bandung City - Deri Fikri Fauzi; Sri Handayani (PT. Anagata Sembagi Education, 2024)
This study explores the application of the STAR Method in teaching English at PAUD Nurnaima Kota Bandung using a qualitative approach and a case study design. Over two months, the research involved two lecturers and five students, collecting data from two PAUD Tutors and the Head of School. The results indicate that integrating English language material through various forms of play—such as role play, motor play, and construction play—not only enhances children's engagement but also accelerates their understanding of new vocabulary. Children demonstrated a good ability to recognize basic vocabulary, influenced by their habit of watching English-language videos. The findings also suggest that learning activities involving physical movement are more effective in improving vocabulary retention. Overall, the implementation of the STAR Method successfully created a fun and engaging learning environment, providing valuable insights for educators and practitioners about the importance of collaboration between educators and parents, while also encouraging the development of more innovative teaching methodologies at the PAUD level.